Just-in-Time Adaptive Interventions for Suicide Prevention: Promise, Challenges, and Future Directions. Issue 4 (2nd October 2022) - Coppersmith, Daniel D.L.; Dempsey, Walter; Kleiman, Evan M.; Bentley, Kate H.; Murphy, Susan A.; Nock, Matthew K.
Abstract : The suicide rate (currently 14 per 100, 000) has barely changed in the United States over the past 100 years. There is a need for new ways of preventing suicide. Further, research has revealed that suicidal thoughts and behaviors and the factors that drive them are dynamic, heterogeneous, and interactive. Most existing interventions for suicidal thoughts and behaviors are infrequent, not accessible when most needed, and not systematically tailored to the person using their own data (e.g., from their own smartphone). Advances in technology offer an opportunity to develop new interventions that may better match the dynamic, heterogeneous, and interactive nature of suicidal thoughts and behaviors. Just-In-Time Adaptive Interventions (JITAIs), which use smartphones and wearables, are designed to provide the right type of support at the right time by adapting to changes in internal states and external contexts, offering a promising pathway toward more effective suicide prevention. In this review, we highlight the potential of JITAIs for suicide prevention, challenges ahead (e.g., measurement, ethics), and possible solutions to these challenges.